2011
DOI: 10.1088/0004-6256/141/3/83
|View full text |Cite
|
Sign up to set email alerts
|

KEPLERECLIPSING BINARY STARS. I. CATALOG AND PRINCIPAL CHARACTERIZATION OF 1879 ECLIPSING BINARIES IN THE FIRST DATA RELEASE

Abstract: The Kepler space mission is devoted to finding Earth-size planets orbiting other stars in their habitable zones. Its large, 105 deg 2 field of view features over 156,000 stars that are observed continuously to detect and characterize planet transits. Yet, this high-precision instrument holds great promise for other types of objects as well. Here we present a comprehensive catalog of eclipsing binary stars observed by Kepler in the first 44 days of operation, the data being publicly available through MAST as of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
418
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 505 publications
(440 citation statements)
references
References 50 publications
10
418
1
Order By: Relevance
“…The percentage of EBs in our sample is high. Prša et al (2011) reported a 1.2% occurence rate of EBs among the Kepler targets. Figure 8 shows the stars that are not assigned to one of the δ Sct, γ Dor or hybrid star groups in a (T eff , log g)-diagram.…”
Section: Characterization Of the Different Classesmentioning
confidence: 95%
See 1 more Smart Citation
“…The percentage of EBs in our sample is high. Prša et al (2011) reported a 1.2% occurence rate of EBs among the Kepler targets. Figure 8 shows the stars that are not assigned to one of the δ Sct, γ Dor or hybrid star groups in a (T eff , log g)-diagram.…”
Section: Characterization Of the Different Classesmentioning
confidence: 95%
“…Pigulski et al 2009) and is the subject of a dedicated paper based on Kepler data by Szabó et al (2011). Sixty-two stars are known to belong to multiple systems, including at least fourteen eclipsing binaries (EB; KIC 1432149, Hartman et al 2004;KIC 10206340, Malkov et al 2006; catalogues by Prša et al 2011;. Seven stars are only known as "(pulsating) variable stars".…”
Section: Sample Stars In the Literaturementioning
confidence: 99%
“…Recently, a list of binaries in the Kepler Q1 data was made available by Prša et al (2011). Since they only focused on binaries and used dedicated methods to detect them, we compared our sample of binaries with their results.…”
Section: Class Statisticsmentioning
confidence: 99%
“…Understanding the dependence of the fidelity and completeness of such future samples on parameters such as period, spectral type, and BEER-model score might enable using these samples to derive some statistical properties of the short-period binary population, like the period distribution, even before RV follow-up is done. Merging wellcorrected large samples of CoRoT and Kepler beaming binaries with equivalent EB samples (e.g., Prša et al 2011) might create large and well-defined samples of short-period binaries, which may shed some light on binary formation and evolution. Radial-velocity follow-up observations of beaming and eclipsing binaries will continue to play a key role in these efforts because in most cases this is the only way to measure their mass ratio and the mass of the secondary companion.…”
Section: Mass Ratio and Orbital Period Distribution Of The Beer Corotmentioning
confidence: 99%